Excision of the ulnar head in patients with rheumatoid arthritis. - Rasker, J J (1980)
In 40 patients with rheumatoid arthritis 43 operations for excision of the ulnar head were performed. A follow-up study was performed after 35 months. In 38 patients wrist pain had disappeared completely or almost completely. The function in use, supination and pronation of the wrists, and wrist strength had all much improved. The stability of the radiocarpal joint was good after operation. Only minor complications were seen.